A cost effectiveness analysis of the preferred antidotes for acute paracetamol poisoning patients in Sri Lanka - Senarathna, Ganga; Ranganathan, Shalini; Buckley, Nick; Fernandopulle, Rohini (BioMed Central Ltd., 2012)
Background: Acute paracetamol poisoning is a rapidly increasing problem in Sri Lanka. The antidotes are expensive and yet no health economic evaluation has been done on the therapy for acute paracetamol poisoning in the developing world. The aim of this study is to determine the cost effectiveness of using N-acetylcysteine over methionine in the management of acute paracetamol poisoning in Sri Lanka. Methods:Economic analysis was applied using public healthcare system payer perspective. Costs were obtained from a series of patients admitted to the National Hospital of Sri Lanka with a history of acute paracetamol overdose. Evidence on effectiveness was obtained from a systematic review of the literature. Death due to hepatotoxicity was used as the primary outcome of interest. Analysis and development of decision tree models was done using Tree Age Pro 2008. Results: An affordable treatment threshold of Sri Lankan rupees 1,537,120/death prevented was set from the expected years of productive life gained and the average contribution to GDP. A cost-minimisation analysis was appropriate for patients presenting within 10 hours and methionine was the least costly antidote. For patients presenting 10-24 hours after poisoning, n-acetylcysteine was more effective and the incremental cost effectiveness ratio of Sri Lankan rupees 316,182/life saved was well under the threshold. One-way and multi-way sensitivity analysis also supported methionine for patients treated within 10 hours and n-acetylcysteine for patients treated within 10-24 hours as preferred antidotes.Conclusions: Post ingestion time is an important determinant of preferred antidotal therapy for acute paracetamol poisoning patients in Sri Lanka. Using n-acetylcysteine in all patients is not cost effective. On economic grounds, methionine should become the preferred antidote for Sri Lankan patients treated within 10 hours of the acute ingestion and n-acetylcysteine should continue to be given to patients treated within 10-24 hours.